2000
DOI: 10.1046/j.1440-1738.2000.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Accretion and tectonic erosion processes revealed by the mode of occurrence and geochemistry of greenstones in the Cretaceous accretionary complexes of the Idonnappu Zone, southern central Hokkaido, Japan

Abstract: The Cretaceous accretionary complexes of the Idonnappu Zone in the Urakawa area are divided into five lithological units, four of which contain greenstone bodies. The Lower Cretaceous Naizawa Complex consists of two lithologic units. The Basaltic Unit (B‐Unit) is a large‐scale tectonic slab of greenstone, consisting of depleted tholeiite similar to that of the Lower Sorachi Ophiolite (basal forearc basin ophiolite) in the Sorachi‐Yezo Belt. The Mixed Unit of Naizawa Complex (MN‐Unit) contains oceanic island‐ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…However, sedimentological studies (Iijima, 1959(Iijima, , 1996 imply a confined N-S trending elongate Paleogene fluvial basin in the central Hokkaido on the basis of heavy mineral associations of sediments, which suggests uplift and erosion of the Kamuikotan ultramafic rocks to the east (trench-side). Such deformation of the 'forearc' does not accord with an active basal erosion regime, but may be related with development of trench slope break as a result of voluminous accretion of sediments during the Paleogene (Ueda et al, 2000).…”
Section: Subsequent Confined Subsidence: Transition To Foreland Settingmentioning
confidence: 93%
See 1 more Smart Citation
“…However, sedimentological studies (Iijima, 1959(Iijima, , 1996 imply a confined N-S trending elongate Paleogene fluvial basin in the central Hokkaido on the basis of heavy mineral associations of sediments, which suggests uplift and erosion of the Kamuikotan ultramafic rocks to the east (trench-side). Such deformation of the 'forearc' does not accord with an active basal erosion regime, but may be related with development of trench slope break as a result of voluminous accretion of sediments during the Paleogene (Ueda et al, 2000).…”
Section: Subsequent Confined Subsidence: Transition To Foreland Settingmentioning
confidence: 93%
“…It is noted that the vertical tilting just after sedimentation was not recognized through geologic studies, but has been clearly indicated on the basis of this geochemical modeling study. Synchronous increase in convergence rate of the IzanagiKula Plate (Ueda et al, 2000) based on relative plate motions after Engebretson et al (1985) implies regional tectonic event. However the Cretaceous deformation of the presumed Eurasian margin seems to occur in a confined part of the forearc basins, because the contemporaneous unit in the MITI Yubari borehole does not indicate such a drastic event.…”
Section: Episodic Deformation Of the Cretaceous Eurasian Marginmentioning
confidence: 99%
“…2 (Kimura 1997;Kimura et al 1994). Some evidence for a continuation of more rapid accretion is suggested by more intense metamorphism of ophiolitic units accreted between Aptian and Cenomanian times (Kiyokawa 1992;Ueda et al 2000).…”
Section: East and Southeast Asiamentioning
confidence: 99%
“…The Hakobuchi Formation shows upward-coarsening facies successions formed by progradation of the inner shelf to delta plain systems (Ando 2003), and these were categorized to be outer to inner shelf, shoreface, subordinate estuary, incised valley, river-channel, back-marsh, and floodplain after Takashima et al (2004). Next, the forearc basin was probably uplifted in the early Paleocene as a result of voluminous accretion beneath the subduction zone (e.g., Ueda et al 2000). Burial history of the Hakobuchi Formation (Figure 4a) optimized on the basis of maturation profiles of Ro and T max (Figure 4b) within the upper part of the Yezo Group indicates an extremely high sedimentation rate (1.57 m/1,000 years), which seems to be unrealistic considering the abovementioned sedimentary facies.…”
Section: Resultsmentioning
confidence: 99%